Revisiting Alice Walker's Womanism: New Insights and Interpretations - Chapai, Rajendra Prasad (Dhaulagiri Journal of Contemporary Issues, 2025)
This article examines Alice Walker's concept of womanism as a theoretical framework within feminist theory, emphasizing the issues, problems and circumstances faced by women of color. Womanists endeavor to rectify inequities that are typically overlooked by conventional feminism. Womanism examines who the woman is in isolation rather than in big framework of feminism as it emphasizes the unique experiences and strengths of women within the socio-cultural structure of America that is predominantly racial and patriarchal. It makes an effort to challenge the underlying injustices that mainstream feminism frequently ignores as a response to the perceived limitations of mainstream feminism. It celebrates blackness portraying black women as multifaceted individuals with strengths in beauty, physical and sexual aptitude, motherhood, sisterhood, and wifehood. It places more emphasis on the transition of black women away from violence and vengeance and towards spiritual awakening. Walker's womanism calls on black women to rebel against repressive systems and recover their agency, challenging accepted standards in a racist, sexist, and capitalist society. The article underscores Walker's commitment to portraying the complexities of black womanhood, examining themes of resilience, oppression, and liberation. Walker delves into the inner and outer lives of African American women by choosing womanism over feminism, encouraging female unity in the struggle against sexism and racism. This study observes women's strength and desire to make a departure from traditional societal narratives of racial and patriarchal society of America.